2012
DOI: 10.1128/aem.05773-11
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evolution of a Facultative Thermophile from a Mesophilic Ancestor

Abstract: Experimental evolution via continuous culture is a powerful approach to the alteration of complex phenotypes, such as optimal/ maximal growth temperatures. The benefit of this approach is that phenotypic selection is tied to growth rate, allowing the production of optimized strains. Herein, we demonstrate the use of a recently described long-term culture apparatus called the Evolugator for the generation of a thermophilic descendant from a mesophilic ancestor (Escherichia coli MG1655). In addition, we used who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 67 publications
6
51
0
Order By: Relevance
“…1). Prior to this study, the highest growth temperature for E. coli cells was reported to be around 48.5°C, as achieved by experimental evolution (5,16). Here, we found that the CeHSP17 protein is, at least partially, localized at the E. coli cell envelope (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…1). Prior to this study, the highest growth temperature for E. coli cells was reported to be around 48.5°C, as achieved by experimental evolution (5,16). Here, we found that the CeHSP17 protein is, at least partially, localized at the E. coli cell envelope (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…For example, increased chaperonin expression (47), reduced glycerol transport (48), and altered RNA polymerase activity (46,49) have been found in E. coli strains selected for increased growth at 42°C or for extending the upper limit on growth to as high as 48.5°C. Single mutations are often responsible for most of the improvements in any one evolved strain (48,49), although this pattern would presumably not hold for experiments of longer duration. Some studies have found that E. coli evolved at stressfully high temperature tend to restore their overall gene expression profiles toward the baseline levels corresponding to their ancestor when it is grown the optimal growth temperature of 37°C (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Lenski's experiment is still in progress, reaching 64,000 generations in January 2016, and many similar studies have been performed by other researchers on different microbial species (not only bacteria but also yeasts, phages, or protists) covering basic scientific questions (29,30) or even in directly applicative projects (31). While planktonic cultures offer a simple setup to study the evolution of bacteria (23,28,31,32), several studies have shown that the selective pressures in unstructured conditions differ from those in biofilms (33)(34)(35)(36). For example, homogeneous, well-mixed environments may select against "social" genotypes that secrete costly metabolites, so-called "public goods," and rather favor fast-reproducing selfish individuals (37).…”
mentioning
confidence: 99%